SPG15 protein deficits are at the crossroads between lysosomal abnormalities, altered lipid metabolism and synaptic dysfunction. Issue 16 (21st March 2022) - Marrone, Lara; Marchi, Paolo M; Webster, Christopher P; Marroccella, Raffaele; Coldicott, Ian; Reynolds, Steven; Alves-Cruzeiro, João; Yang, Zih-Liang; Higginbottom, Adrian; Khundadze, Mukhran; Shaw, Pamela J; Hübner, Christian A; et al.
Abstract: Hereditary spastic paraplegia type 15 (HSP15) is a neurodegenerative condition caused by the inability to produce SPG15 protein, which leads to lysosomal swelling. However, the link between lysosomal aberrations and neuronal death is poorly explored. To uncover the functional consequences of lysosomal aberrations in disease pathogenesis, we analyze human dermal fibroblasts from HSP15 patients as well as primary cortical neurons derived from an SPG15 knockout (KO) mouse model. We find that SPG15 protein loss induces defective anterograde transport, impaired neurite outgrowth, axonal swelling and reduced autophagic flux in association with the onset of lysosomal abnormalities. Additionally, we observe lipid accumulation within the lysosomal compartment, suggesting that distortions in cellular lipid homeostasis are intertwined with lysosomal alterations. We further demonstrate that SPG15 KO neurons exhibit synaptic dysfunction, accompanied by augmented vulnerability to glutamate-induced excitotoxicity. Overall, our study establishes an intimate link between lysosomal aberrations, lipid metabolism and electrophysiological impairments, suggesting that lysosomal defects are at the core of multiple neurodegenerative disease processes in HSP15.